2014
DOI: 10.7243/2050-1323-3-2
|View full text |Cite
|
Sign up to set email alerts
|

Growth and functionalization of carbon nanotubes on quartz filter for environmental applications

Abstract: Background: Air pollution has become an important issue worldwide due to its adverse health effects. Among the different air contaminants, volatile organic compounds (VOCs) are liquids or solids with a high vapor pressure at room temperature that are extremely dangerous for human health. Removal of these compounds can be achieved using nanomaterials with tailored properties such as carbon nanotubes. Methods: Vertically-aligned multiwall carbon nanotubes (CNTs) were successfully grown on quartz filters by means… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 46 publications
2
5
0
Order By: Relevance
“…MWCNTs (110-170 nm) revealed very short bres and large diameters, as anticipated (Fig. 5,36 The increased dispersion of MWCNTs in water proved the successful oxidation of MWCNTs. Atomic force microscopy (AFM) studies have shown that there is an insignicant decrease in length following the oxidation process.…”
Section: Characterization Of Pristine Mwcnts and Omwcntssupporting
confidence: 76%
See 2 more Smart Citations
“…MWCNTs (110-170 nm) revealed very short bres and large diameters, as anticipated (Fig. 5,36 The increased dispersion of MWCNTs in water proved the successful oxidation of MWCNTs. Atomic force microscopy (AFM) studies have shown that there is an insignicant decrease in length following the oxidation process.…”
Section: Characterization Of Pristine Mwcnts and Omwcntssupporting
confidence: 76%
“…1 The two forms of CNTs are the single-walled carbon nanotubes (SWCNTs) and the multi-walled carbon nanotubes (MWCNTs), which are formed from either a single roll or several cylindrical shells of graphene sheet, respectively. 5 However, especially in aqueous environments their application has been limited due to their strong van der Waals forces leading to agglomeration. 5 However, especially in aqueous environments their application has been limited due to their strong van der Waals forces leading to agglomeration.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These formed agglomerates were special feature found on collecting emissions from this CNT synthesis on such hydrophilic filter fibers. The results found here, and this interpretation of the methodology for structure formation, are consistent with the results of Amade et al, who found similar structures when directly depositing untreated hydrophobic CNTs onto quartz fibers (Amade et al, 2014).…”
Section: Collection Of Exhaust Particles On Filterssupporting
confidence: 82%
“…Carbon nanotubes deposited on quartz filters used to eliminate and monitor the VOCs and other air pollutants by out by π-π interactions (Fig. 4) [17].Nano-adsorptive materials acting as a -super adsorbent‖ for several air pollutants like harmful gases and volatile organics via [18]:…”
Section: Adsorptionmentioning
confidence: 99%